APLIKASI COMMODITY SYSTEM ASSESSMENT METHOD (CSAM) PADA PENANGANAN PASCAPANEN SAWI HIJAU (Brassica rapa I. Subsp. Perviridis Bayley) DARI PETANI DI KECAMATAN BANJARANGKAN SAMPAI PENGECER - Kayana Putera, I Made Dwi; Lani Triani, I.G.A; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni, 2016)
This research were aimed to 1) investigate amount of green mustard distribution lanes from the farmers in Banjarangkan District to the retailers 2) to investigate kind of distribution lanes and post harvest handling at each distribution lanes of green mustard and 3) to investigate Pb and Cd content in green mustard which was distributed from the farmers at Banjarangkan District to the retailers. The study used a survey method with the application of CSAM in the form of questionnaire distributed to farmers, collectors, wholesalers, and retailers green mustard. Laboratory analysis using AAS to determine the levels of Pb and Cd in green mustard. There were four distribution lanes of green mustard from farmer at Banjarangkan District to Retailers, namely lane 1 (farmer ? retailer), lanes II (farmer ? collector ? retailer), lanes III (farmer ? collector ? wholesaler ? retailer) and lanes IV (farmer ? collector ? retailer). Postharvest handling at the farm include harvesting, sorting, weighing and transporting, postharvest handling at the suppliers and wholesalers includes sorting and transporting, postharvest handling at the retail includes sorting and display. Impact on postharvest loss of green mustard at farm were on process of sorting reached 12%. At suppliers level was on the sorting reached 4 % (not significant) at the traders was on sorting process reached 6% (significant). Loss impact on retail level was on the display reached 12% (significant). The concentration of heavy metal Pb and Cd on lane I ranged of 0,4768–0,4966 mg/kg and 0,4718–0.4768 mg/kg; in the lane II ranged of 0,3675–0.4519 mg/kg and 0.4867–0.5562 mg/kg; in the lane III ranged of 0.3129–0.4023 mg/kg and 0.5016–0.5662 mg/kg; in the lane IV ranged of 0.3923–0.4370 mg/kg and 0.5066–0.5314 mg/kg. Keywords: CSAM application, Concentration of Pb and Cd, green mustard
Keywords: 100